Unique Challenges in Development, Psychometric Evaluation, and Interpretation of Daily and Event Diaries as Endpoints in Clinical Trials. (November 2015) - Gater, Adam; Coon, Cheryl D.; Nelsen, Linda M.; Girman, Cynthia
By bringing data collection closer to real time and minimizing recall bias, patient diaries or event-driven logs offer substantial benefits over retrospective questionnaires for many patient-reported disease concepts. Such assessments are increasingly used to support primary and secondary endpoints in randomized controlled trials. These diaries have the potential to provide more reliable and valid assessment of patients' subjective experiences of symptoms and disease events. However, use of such diaries presents significant and unique challenges depending on the context of use. Of note, while symptom-related label claims are those most frequently granted by regulatory authorities, no guidance specific to support the development, psychometric evaluation, and interpretation of endpoints derived from patient diaries exists. This article provides an overview of key methodological, statistical, and clinical considerations for implementation of patient diaries with a regulatory perspective in mind. Approaches and solutions covered in this article include (1) techniques to establish content validity based on obtaining qualitative insights in naturalistic settings and real-life experience of diary completion, (2) demonstration of psychometric properties with respect to day-to-day variability, and (3) aggregation of data from multiple days/events to move from items to endpoints. The importance of the patients' engagement is highlighted in order to help overcome these challenges throughout all stages of diary and endpoint development and evaluation. This article can inform researchers who are developing or implementing patient diaries as clinical trial endpoints to ensure that the nuances of this mode of data collection are considered in the development of endpoints and prior to regulatory interactions.